Investigation of the Synthesis and Properties of Ternary V–Cu–Ce Oxides of Composition VCuCeO - Christothea Attipa; Charis R. Theocharis (Adsorption Science & Technology)
A co-precipitation method has been used to prepare ternary mixed oxides based on ceria with the general formula V x Cu x Ce 1 – 2x O 2 , where x was varied between 0.05 and 0.45. The structural and surface properties as well as the morphologies of the solids were examined by thermogravimetric analysis, differential scanning calorimetry, X-ray diffraction studies, nitrogen adsorption isotherms, Fourier-transform infrared spectroscopy and scanning electron microscopy. For samples where the vanadium and copper content was low (x ≤ 0.3), the surface area increased and the pore distribution shifted towards the micropore range. The sample V 0.05 Cu 0.05 Ce 0.9 O 2 exhibited the highest surface area and the sample V 0.45 Cu 0.45 Ce 0.1 O 2 the smallest. The samples were calcined within the temperature range 473–1073 K. When the vanadium content was increased to x ≥ 0.3 and the calcination temperature set at 673 K, a phase with composition CeVO 4 was detected via X-ray diffractometry, in addition to a V 2 O 5 and a CeO 2 phase. The FT-IR spectra confirmed the above results.